2020
DOI: 10.1051/e3sconf/202019601004
|View full text |Cite
|
Sign up to set email alerts
|

Earth electric field negative anomalies as earthquake precursors

Abstract: In fair weather conditions, electric field potential gradient in the near-ground air takes positive values. Negative anomalies occur under the influence of different ionizing processes such as galactic cosmic ray flux and radioactive gas emanation from the ground. In the conditions of calm geomagnetic state and fair weather, anomalies can be used for earthquake forecast. In the paper, the efficiency of earthquake forecast based on negative anomalies is under the study. It was obtained that the efficiency of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Choudhury et al [70] observed that prior to the earthquake, a bay-like variation in the magnitude of kilovolts existed in the vertical electric field. More studies have observed that the persistent negative anomalies in the magnitude of kilovolts in the atmospheric electric field occurred before earthquakes, and the authors of these studies claimed that they may be potential precursor signals of earthquakes [71,72]. Based on existing research into atmospheric electric field anomalies, we try to explain the generation mechanism of this negative abnormal signal.…”
Section: Discussionmentioning
confidence: 99%
“…Choudhury et al [70] observed that prior to the earthquake, a bay-like variation in the magnitude of kilovolts existed in the vertical electric field. More studies have observed that the persistent negative anomalies in the magnitude of kilovolts in the atmospheric electric field occurred before earthquakes, and the authors of these studies claimed that they may be potential precursor signals of earthquakes [71,72]. Based on existing research into atmospheric electric field anomalies, we try to explain the generation mechanism of this negative abnormal signal.…”
Section: Discussionmentioning
confidence: 99%
“…[47], the daily variations of TEC in the ionosphere and the daily energy released near three studied earthquakes were examined and correlated, confirming a minor correlation. It was deduced that more parameters are essential to understand the cause of ionospheric TEC anomalies [48].…”
Section: Electron Density and Tec Anomaliesmentioning
confidence: 99%
“…Many other studies correlated earthquake occurrences with other variables, such as the Land Surface Temperature (LST) [15]- [17], the Surface Latent Heat Flux (SLHF) [18], the Outgoing Longwave Radiation (OLR) [19], the geomagnetic and electric fields [19]- [21], and the Schumann resonance [22], [23].…”
Section: Introductionmentioning
confidence: 99%